(untitled) (Indian Journal of Animal Production and Management, 2024)
India possesses maximum number of cows and buffaloes in the world and her countrymen rear them mainly for harvesting their milk. Likewise India also possesses other livestock, like sheep, goat, equines, pigs, camel, rabbit, poultry as well as wild animals in large numbers. Rearing of a particular species requires rearing of different classes of animals at the farm, for cattle: in-milk cows, suckling calves, heifers, pregnant heifers, down calvers, dry non pregnant cows, dry pregnant cows, bull calves, bulls, bullocks, old stock and so on, preferably in their respective houses. However, all these categories of cattle may not be available at a small sized farm.